Heterogeneous rhodium-tin nanoparticles: highly active and durable electrocatalysts for the oxidation of ethanol - Ahn, Minjeh; Cha, In Young; Lee, Joong Kee; Yoo, Sung Jong; Sung, Yung-Eun (ROYAL SOC CHEMISTRY, 2015)
Facile synthesis of Rh-Sn catalysts for the electrocatalytic oxidation of ethanol is carried out via a surfactant-free microwave-assisted method. The bifunctional mechanism and electronic modification with C-C bond splitting enable this electrocatalyst to be remarkably active and durable at high fuel concentrations, which allows for a significant reduction in the volume and weight of the fuel cell system.
Keywords: ALKALINE MEDIA; OXIDIZING ETHANOL; POLYOL SYNTHESIS; FUEL-CELLS; C-C; ELECTROOXIDATION; PLATINUM; METAL; NANOCRYSTALS; CARBON